Monocotyledons Series 5 : Monocotyledon Plants of Peat Swamp Forest of Sarawak - Meekiong, Kalu (Forest Department Sarawak, 2024)
This is the fifth book in The Sarawak’s Monocotyledon Plant Series publication under the Monocotyledon Plant Project. The Monocotyledon Plants of Peat Swamp Forests is a book that specifically on the selected common monocot plants found in the peat swamp forests of Sarawak, particularly in the Heat of Borneo areas. Other books in this Monocotyledons Series are, (1) A Checklist From Western Sarawak, (2) Gingers of Sarawak’s Heart of Borneo, (3) The Genus Zingiber, and (4) Palms of Sarawak. Preliminary documentation recorded a total of 28 families, 90 genera, and more than 130 species have been recorded in the peat swamp forests in Sarawak. The families Orchidaceae, Arecaceae, Araceae, Zingiberaceae, and Cyperaceae are very dominant. Our documentation on the Monocotyledon plants in Sarawak is beyond complete. Many works are needed, especially on the field excursions and sample collections.